"The Dust Was Long in Settling": Human Capital and the Lasting Impact of the American Dust Bowl. (3rd April 2018) - Arthi, Vellore
Abstract : I find that childhood exposure to the Dust Bowl, an environmental shock to health and income, adversely impacted later-life human capital—especially when exposure was in utero —increasing poverty and disability rates, and decreasing fertility and college completion rates. The event's devastation of agriculture, however, had the beneficial effect of increasing high school completion, likely by pushing children who otherwise might have worked on the farm into secondary schooling. Lastly, New Deal spending helped remediate Dust Bowl damage, suggesting that timely and substantial policy interventions can aid in human recovery from natural disasters.